PSYCHOLOGICAL SUPPORT OF THE PHENOMENON OF RELIGIOUS BELIEF - Климишин, О. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article presents the author's argument of four planes of theorizing of religious faith as psychospiritual phenomenon: religious faith – the unconscious, religious belief – the cognitive sphere, religious faith – the emotional sphere, religious belief – the volitional sphere.